Lithostratigraphy and petrography of the Monte Banchetta-Punta Rognosa oceanic succession (Troncea and Chisonetto Valleys, Western Alps) - Corno, Alberto; Mosca, Pietro; Borghi, Alessandro; Gatteggio, Marco (Ofioliti, 2019)
This paper describes lithostratigraphy and Alpine tectono-metamorphic evolution of the oceanic succession of the Monte Banchetta-Punta Rognosa unit (Italian Western Alps). The oceanic substratum consists of serpentinized peridotites covered by ophicarbonates, documenting therefore exhumation and exposure of the upper mantle at the seafloor in Jurassic times. Upwards, the sedimentary cover begins with polymictic metabreccias and intercalated siliciclastic sediments (considered Late Jurassic - Early Cretaceous in age), both containing oceanic and continental detritus, and interpreted as mass-flow deposits on sea floor. Then, the upper part of the cover consists of Cretaceous pelagic carbonate sediments (calcschists), lying over a main unconformity. The stratigraphic features and the architecture of the sedimentary cover suggest that this segment of the Piemonte-Liguria Ocean was in a proximal position with respect to the rifted margins. In a general context of the ocean-continent transition, source areas for continental detritus can be envisaged on the hyperextended part of the European margin or on its more proximal part, adjacent to structural highs made of oceanic mantle, as recorded by oceanic detritus. The combination of structural, petrographic and mineral chemistry data defined the Alpine prograde and retrograde metamorphic evolution of this oceanic segment. The metamorphic peak was reached during the D1 event at the transition between lawsonite- and epidote- blueschist facies conditions. Then, a first decompressional event D2 always at blueschist facies conditions was followed by a D3 event at green schist facies conditions.